O trabalho flexível no comércio varejista: multifuncionalidade e precarização - Santos, Silvio Matheus Alves (2013)
This dissertation dealt with job in the multinacional fast fashion retail. The research analysed speeches of permanent workers, that make part of an organization of flexible working, logic skills and multifunctionality, in search of targets in the carrier plan. In this context, we realized the process of job insecurity and work intensification when workers assume the responsability of personal and professional targets set by the enterprise. We also observed the impacts on their physical and psychological health. As results, we noticed that the work intensifies and become complex with the increasing of demand in celebratory events. Moreover, there are an increase of responsability and accumulation of tasks that appears according to the carrier plan. The research was made in two C& A stores in Aracaju-Sergipe in 2011. It was conducted through interviews with the workers, observations during working time, raising of materials and public documentation about the enterprise.